Artificial Intelligence Theory in Service Management - Reis, João (2020)
Artificial intelligence (AI) is expected to be more promising in the coming years, with, for example, notable gains in productivity, although there may be a significant impact on job reduction, which may jeopardize labor sustainability. Accordingly, there is a need to better understand this phenomenon and to analyze it in the light of a particular theory. However, there is a scarcity of AI theories in the service management literature. In order to obtain a better understanding of the subject, we have conducted a systematic review of the literature to provide a comprehensive analysis of the theories developed regarding AI in service management. The results have showed a wide range of theories, but not all directly related with AI; the latter are smaller in number making it difficult to draw a clear pattern. At current days, researchers are slowly advancing with new AI theories and moving away from those already in use, such as in computer science, ethics, philosophical theories, and so on.